Laser-induced switching of the biological activity of phosphonate molecules - Kolesnikov, Ilya; Khokhlova, Anastasia; Pankin, Dmitry; Pilip, Anna; Egorova, Anastasia; Zigel, Vladislav; Gureev, Maxim; Leuchs, Gerd; Manshina, Alina (New Journal of Chemistry, 2021)
Butyrylcholinesterase inhibition and its enhancement as a result of laser irradiation are demonstrated for the first time for a series of phosphorylated arylaminomalonates. The effect of substituents in the phenyl group on butyrylcholinesterase inhibition and its laser-activated enhancement is revealed experimentally and confirmed by molecular dynamics and docking modelling.
CRIS-Team Scopus Importer:2023-04-20